Length of work improves nurse performance - Yustina Kristianingsih; Sri Winarni; Ana Kustyorini (University of Muhammadiyah Malang, 2022)
Introduction: Performance is the result of the work of personnel in the organization both in quality and quantity, one of which is the implementing nurse, the phenomenon that is obtained in one of the private hospitals in the city of Surabaya is that the performance of the implementing nurse is still less than optimal by implementing nurses who have different tenures. Objectives: The purpose of this study was to identify the relationship between the length of service and the performance of nurses. Methods: The research design used was correlational with a cross-sectional approach. The sampling technique used simple random sampling with a total sample of 59 nurses who met the inclusion criteria. Data were analyzed using Spearman's rank with α = 0.05. Results: The results showed that the length of work of the implementing nurse in the inpatient room was 57.6% 5-10 years. The performance of the implementing nurse in the inpatient room is 64.4% excellent, and the results of the statistical test with the Spearman rank obtained p = 0.031, which means that there is a relationship between the length of work and the performance of the implementing nurse in the inpatient room. Conclusions: This study hoped that the nursing management of private hospitals in the city of Surabaya is expected to provide good rewards for implementing nurses to feel comfortable and loyal at work so that they can improve the performance of implementing nurses.